Low-shrinkage anti-cracking material additive
By using low-shrinkage crack-resistant material additives in concrete, combined with straw powder composite and modified fiber composite, the problem of poor crack resistance of concrete is solved, and better crack resistance and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411876445.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, concrete has poor crack resistance and is difficult to effectively solve the emergence and development of early cracks.
A low-shrinkage-resistant material additive is used, which consists of straw powder composite and modified fiber composite. The fiber toughness is enhanced and interface adhesion is improved by modification of sodium silicate nohydrate.
It significantly improves the crack resistance and mechanical properties of concrete, reduces the generation of interfacial cracks, and improves the overall strength and toughness of concrete.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a low shrinkage and crack-resistant material additive. Background Art
[0002] Concrete is a general term for engineering composite materials that are cemented into a whole by cementitious materials. Concrete is usually made of cement as a cementitious material, sand and stone as aggregates, and water (which may contain admixtures and additives) in a certain proportion. Cement concrete, also known as ordinary concrete, is obtained by mixing and mixing. It is widely used in civil engineering.
[0003] Concrete has the characteristics of abundant raw materials, low price and simple production process, so its usage is increasing. At the same time, concrete also has the characteristics of high compressive strength, good durability and wide range of strength grades. These characteristics make it widely used. It is not only used in various civil engineering projects, but also in shipbuilding, machinery industry, marine development, geothermal engineering, etc. Concrete is also an important material. During the hydration and hardening process of cement concrete, its own hydration reaction and water exchange with the surrounding environment cause concrete to shrink and dry. Common maintenance measures such as covering (wet sacks or plastic films), water storage maintenance, and sprinkling can only protect the surface concrete. Due to the low permeability coefficient of modern concrete, it is difficult for water to penetrate into the interior of the concrete, and common maintenance measures have limited effect on reducing concrete shrinkage. Adding expansion agent to the mix ratio to compensate for the volume shrinkage of concrete is a more direct way to solve its autogenous volume shrinkage. However, this method ignores the generation and development of cracks in the early stage of hydration reaction. The problem of concrete cracks is difficult to solve at this stage mainly because the generation of cracks is not noticed in the early stage, and the cracks will continue to extend along the structure.
[0004] Patent technical document CN109485299B discloses a multi-effect concrete structure self-waterproofing additive with self-repairing ability, which is composed of the following raw materials in percentage by mass: 40%-60% expansion agent, 2%-6% aluminum oxide, 2%-5% zinc sulfate, 7%-15% water retaining agent, 4%-12% modified fluorine-containing silicone oil, 12%-26% anti-cracking fiber, and 2%-8% modified terephthalic acid multivalent metal salt. The multi-effect concrete structure self-waterproofing additive with self-repairing ability prepared by this method can not only improve the dispersibility of various raw materials in concrete, reduce the porosity in concrete, and increase the compactness of concrete, but also improve its water retention performance, but its anti-cracking performance is poor.
[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a low shrinkage anti-cracking material additive. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a low shrinkage anti-cracking material additive to solve the problem of poor anti-cracking performance of concrete in the prior art.
[0007] Based on the above purpose, the present invention provides a low shrinkage anti-cracking material additive.
[0008] A low shrinkage and crack-resistant material additive, comprising the following raw materials in parts by weight: 20-25 parts of straw powder compound, 15-20 parts of modified fiber compound, 45-50 parts of fly ash, 15-30 parts of rice husk ash, 6-10 parts of water reducer and 18-22 parts of expansion agent;
[0009] The straw powder composite is prepared from sodium silicate nonahydrate, wheat straw, corn straw and rice straw;
[0010] The modified fiber composite is prepared from polypropylene fiber, polyester fiber, basalt fiber and mesoporous silica.
[0011] Preferably, the preparation method of the straw powder composite is as follows:
[0012] Step A1. Cut wheat straw, corn straw and rice straw into small pieces, put them into a grinder, grind them, and dry them at 70-80°C for 3-5h to obtain straw powder;
[0013] Step A2. Sodium silicate nonahydrate is dissolved in water at 28-32°C, and then straw powder is added, reacted for 4-6 hours, stirred at 200-300 rpm for 15-18 minutes every half an hour, and dried at 90-100°C for 5-8 hours to obtain a straw powder composite.
[0014] Preferably, in step A1, the mass ratio of wheat straw, corn straw and rice straw is 30-35:10-15:8-12;
[0015] The particle size of the straw powder in step A1 is 10-30 mm.
[0016] Preferably, the mass ratio of sodium silicate nonahydrate, water and straw powder in step A2 is 8-10:250-300:45-50.
[0017] Preferably, the preparation method of the modified fiber composite is as follows:
[0018] Step B1. Take polypropylene fiber, polyester fiber and basalt fiber, and irradiate them with electron beam to obtain pretreated composite fibers;
[0019] Step B2. Place the silane coupling agent in a 78%-85% ethanol solution, stir at 120-150rpm for 10-15min, then add the mesoporous silica, and continue stirring for 70-80min; then add the pretreated composite fiber, and ultrasonically treat for 40-50min, filter, wash, and dry at 70-80°C for 8-12h to obtain a modified fiber composite.
[0020] Preferably, the mass ratio of the polypropylene fiber, the polyester fiber and the basalt fiber in step B1 is 10-15:10-15:20-30;
[0021] The irradiation dose of the electron beam irradiation in step B1 is 200-250 kGy, and the irradiation time is 8-10 s.
[0022] Preferably, the mass ratio of the silane coupling agent, the ethanol solution, the mesoporous silica and the pretreated composite fiber in step B2 is 55-65:95-105:1-1.5:4.5-5.5.
[0023] Preferably, the water reducer is any one of a polycarboxylate water reducer and a sodium lignin sulfonate water reducer.
[0024] Preferably, the expansion agent is any one of a calcium oxide expansion agent, a CSA expansion agent and a UEA expansion agent.
[0025] Preferably, the preparation method of the low shrinkage anti-cracking material additive is as follows:
[0026] The straw powder composite, modified fiber composite, fly ash and rice husk ash are mixed, stirred at 100-200 rpm for 10-15 minutes, and then a water reducer and an expansion agent are added, and stirred at 100-200 rpm for 10-15 minutes to obtain a low shrinkage anti-cracking material additive.
[0027] Beneficial effects of the present invention:
[0028] The invention provides a low shrinkage anti-cracking material additive. The invention adds a straw powder compound and a modified fiber compound, so that the prepared low shrinkage anti-cracking material additive has better anti-cracking ability and mechanical properties in the application of concrete; the straw powder compound is prepared from sodium silicate nonahydrate, wheat straw, corn straw and rice straw; the sodium silicate nonahydrate can form a uniform and dense protective layer on the surface of the straw, and penetrate into the internal pores of the straw to increase the density of the material, and synergizes with cellulose in the modification process, thereby enhancing the toughness of the fiber; at the same time, the sodium silicate nonahydrate can improve the interface adhesion between the fiber and the matrix, and reduce the generation of interface cracks, so that the mechanical properties of the prepared concrete are significantly improved;
[0029] The modified fiber composite provided by the present invention is prepared from polypropylene fiber, polyester fiber, basalt fiber and mesoporous silica. The polypropylene fiber, polyester fiber and basalt fiber can play a certain degree of reinforcement role and inhibit the formation of shrinkage cracks. The mesoporous silica modified fiber effectively improves the bonding force of concrete due to the large specific surface area of mesoporous silica. The straw powder composite and the modified fiber composite synergize with the expansion agent and the water reducer to improve the crack resistance, and have broad application prospects. DETAILED DESCRIPTION
[0030] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0031] The sources and properties of some of the raw materials used in the present invention are as follows:
[0032] Sodium silicate nonahydrate was purchased from Nanjing Chemical Reagent Co., Ltd.; polypropylene fiber was purchased from Shandong Yonglida New Materials Technology Co., Ltd.; polyester fiber was purchased from Shandong Yonglida New Materials Technology Co., Ltd.; basalt fiber was purchased from Shandong Oude Chemical Fiber Products Co., Ltd.; silane coupling agent model is silane coupling agent KH560, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; polycarboxylic acid water reducer was purchased from Liaoning Kelong Fine Chemical Co., Ltd.; lignin sulfonate sodium salt water reducer was purchased from Linzhang County Chenghe Building Materials Co., Ltd.; calcium oxide expansion agent was purchased from Henan Juneng Hezhong Special Materials Co., Ltd.; CSA expansion agent was purchased from Nanjing Yaojie Energy Saving Technology Co., Ltd.; UEA expansion agent was purchased from Hubei Chengfeng Chemical Co., Ltd.
[0033] Example 1: A low shrinkage anti-cracking material additive, comprising the following preparation steps:
[0034] S1. 30 g wheat straw, 10 g corn straw and 8 g rice straw were cut into small pieces, crushed in a grinder, and dried at 70 ° C for 3 h to obtain straw powder, wherein the particle size of the straw powder was 10 mm;
[0035] S2. 8 g of sodium silicate nonahydrate was dissolved in 250 g of water at 28 ° C, followed by addition of 45 g of straw powder, reaction for 4 h, stirring at 200 rpm for 15 min every half an hour, and drying at 90 ° C for 5 h to obtain a straw powder composite;
[0036] S3. Take 10g of polypropylene fiber, 10g of polyester fiber and 20g of basalt fiber and irradiate with electron beam to obtain a pretreated composite fiber, wherein the irradiation dose of electron beam irradiation is 200kGy and the irradiation time is 8s;
[0037] S4. 55 g of silane coupling agent was placed in 95 g of 78% ethanol solution, stirred at 120 rpm for 10 min, and then 1 g of mesoporous silica was added, and stirring was continued for 70 min; then 4.5 g of pretreated composite fiber was added, and ultrasonic treatment was performed for 40 min, filtered, washed, and dried at 70 ° C for 8 h to obtain a modified fiber composite;
[0038] S5. 20g of straw powder composite, 15g of modified fiber composite, 45g of fly ash, and 15g of rice husk ash were mixed, stirred at 100rpm for 10min, and then 6g of polycarboxylate water reducer and 18g of calcium oxide expansion agent were added, and stirred at 100rpm for 10min to obtain a low shrinkage anti-cracking material additive.
[0039] Embodiment 2: A low shrinkage anti-cracking material additive, comprising the following preparation steps:
[0040] S1. 31 g of wheat straw, 11 g of corn straw and 8.5 g of rice straw were cut into small pieces, crushed in a grinder, and dried at 72°C for 3.5 h to obtain straw powder, wherein the particle size of the straw powder was 12 mm;
[0041] S2. 8.5 g of sodium silicate nonahydrate was dissolved in 260 g of water at 29 ° C, followed by the addition of 46 g of straw powder, reacted for 4.5 h, stirred at 220 rpm for 15.5 min every half an hour, and dried at 92 ° C for 5.5 h to obtain a straw powder composite;
[0042] S3. Take 11g polypropylene fiber, 11g polyester fiber and 22g basalt fiber, and irradiate with electron beam to obtain pretreated composite fiber, wherein the irradiation dose of electron beam irradiation is 210kGy, and the irradiation time is 8.5s;
[0043] S4. 56 g of silane coupling agent was placed in 96 g of 80% ethanol solution, stirred at 125 rpm for 11 min, and then 1.1 g of mesoporous silica was added, and stirring was continued for 72 min; then 4.6 g of pretreated composite fiber was added, and ultrasonic treatment was performed for 42 min, filtered, washed, and dried at 72 ° C for 9 h to obtain a modified fiber composite;
[0044] S5. 21g of straw powder composite, 16g of modified fiber composite, 46g of fly ash and 18g of rice husk ash were mixed, stirred at 120rpm for 11min, and then 7g of polycarboxylic acid water reducer and 19g of CSA expansion agent were added, and stirred at 120rpm for 11min to obtain a low shrinkage anti-cracking material additive.
[0045] Embodiment 3: A low shrinkage anti-cracking material additive, comprising the following preparation steps:
[0046] S1. 32 g of wheat straw, 12 g of corn straw and 9 g of rice straw were cut into small pieces, crushed in a grinder, and dried at 74 ° C for 4 h to obtain straw powder, wherein the particle size of the straw powder was 14 mm;
[0047] S2. 9 g of sodium silicate nonahydrate was dissolved in 270 g of water at 30 ° C, followed by the addition of 47 g of straw powder, reacted for 5 h, stirred at 240 rpm for 16 min every half an hour, and dried at 94 ° C for 6 h to obtain a straw powder composite;
[0048] S3. Take 12g of polypropylene fiber, 12g of polyester fiber and 24g of basalt fiber and irradiate with electron beam to obtain a pretreated composite fiber, wherein the irradiation dose of electron beam irradiation is 220kGy and the irradiation time is 9s;
[0049] S4. 58 g of silane coupling agent was placed in 98 g of 81% ethanol solution, stirred at 130 rpm for 12 min, and then 1.2 g of mesoporous silica was added, and stirring was continued for 74 min; then 4.8 g of pretreated composite fiber was added, and ultrasonic treatment was performed for 44 min, filtered, washed, and dried at 74 ° C for 10 h to obtain a modified fiber composite;
[0050] S5. 22g of straw powder composite, 17g of modified fiber composite, 47g of fly ash and 20g of rice husk ash were mixed, stirred at 140rpm for 12min, then 8g of polycarboxylate water reducer and 20g of CSA expansion agent were added, and stirred at 140rpm for 12min to obtain a low shrinkage anti-cracking material additive.
[0051] Embodiment 4: A low shrinkage anti-cracking material additive, comprising the following preparation steps:
[0052] S1. 33 g of wheat straw, 13 g of corn straw and 10 g of rice straw were cut into small pieces, crushed in a grinder, and dried at 76 ° C for 4 h to obtain straw powder, wherein the particle size of the straw powder was 20 mm;
[0053] S2. 9 g of sodium silicate nonahydrate was dissolved in 280 g of water at 30 ° C, followed by the addition of 48 g of straw powder, reacted for 5 h, stirred at 260 rpm for 16.5 min every half an hour, and dried at 96 ° C for 6.5 h to obtain a straw powder composite;
[0054] S3. Take 13g polypropylene fiber, 13g polyester fiber and 26g basalt fiber, and irradiate with electron beam to obtain pretreated composite fiber, wherein the irradiation dose of electron beam irradiation is 230kGy, and the irradiation time is 9s;
[0055] S4. 60 g of silane coupling agent was placed in 100 g of 82% ethanol solution, stirred at 135 rpm for 13 min, and then 1.3 g of mesoporous silica was added, and stirring was continued for 76 min; then 5 g of pretreated composite fiber was added, and ultrasonic treatment was performed for 46 min, filtered, washed, and dried at 76 ° C for 10 h to obtain a modified fiber composite;
[0056] S5. 23g of straw powder composite, 18g of modified fiber composite, 48g of fly ash and 22g of rice husk ash were mixed, stirred at 160rpm for 13min, then 9g of sodium lignin sulfonate water reducer and 21g of UEA type expansion agent were added, and stirred at 160rpm for 13min to obtain a low shrinkage anti-cracking material additive.
[0057] Example 5: A low shrinkage anti-cracking material additive, comprising the following preparation steps:
[0058] S1. 34 g wheat straw, 14 g corn straw and 11 g rice straw were cut into small pieces, crushed in a grinder, and dried at 78°C for 4.5 h to obtain straw powder, wherein the particle size of the straw powder was 25 mm;
[0059] S2. 9.5 g of sodium silicate nonahydrate was dissolved in 290 g of water at 31 ° C, followed by the addition of 49 g of straw powder, reacted for 5.5 h, stirred at 280 rpm for 17 min every half an hour, and dried at 98 ° C for 7 h to obtain a straw powder composite;
[0060] S3. Take 14g polypropylene fiber, 14g polyester fiber and 28g basalt fiber, and irradiate with electron beam to obtain pretreated composite fiber, wherein the irradiation dose of electron beam irradiation is 240kGy, and the irradiation time is 9.5s;
[0061] S4. 62 g of silane coupling agent was placed in 102 g of 83% ethanol solution, stirred at 140 rpm for 14 min, and then 1.4 g of mesoporous silica was added, and stirring was continued for 78 min; then 5.2 g of pretreated composite fiber was added, and ultrasonic treatment was performed for 48 min, filtered, washed, and dried at 78 ° C for 11 h to obtain a modified fiber composite;
[0062] S5. 24g of straw powder composite, 19g of modified fiber composite, 49g of fly ash and 25g of rice husk ash were mixed, stirred at 180rpm for 14min, then 10g of sodium lignin sulfonate water reducer and 22g of UEA type expansion agent were added, and stirred at 180rpm for 14min to obtain a low shrinkage anti-cracking material additive.
[0063] Example 6: A low shrinkage anti-cracking material additive, comprising the following preparation steps:
[0064] S1. 35 g wheat straw, 15 g corn straw and 12 g rice straw were cut into small pieces, crushed in a grinder, and dried at 80 ° C for 5 h to obtain straw powder, wherein the particle size of the straw powder was 30 mm;
[0065] S2. 10 g of sodium silicate nonahydrate was dissolved in 300 g of water at 32 ° C, followed by addition of 50 g of straw powder, reaction for 6 h, stirring at 300 rpm for 18 min every half an hour, and dried at 100 ° C for 8 h to obtain a straw powder composite;
[0066] S3. Take 15g of polypropylene fiber, 15g of polyester fiber and 30g of basalt fiber and irradiate with electron beam to obtain a pretreated composite fiber, wherein the irradiation dose of electron beam irradiation is 250kGy and the irradiation time is 10s;
[0067] S4. 65 g of silane coupling agent was placed in 105 g of 85% ethanol solution, stirred at 150 rpm for 15 min, and then 1.5 g of mesoporous silica was added, and stirring was continued for 80 min; then 5.5 g of pretreated composite fiber was added, and ultrasonic treatment was performed for 50 min, filtered, washed, and dried at 80 ° C for 12 h to obtain a modified fiber composite;
[0068] S5. 25 g of straw powder composite, 20 g of modified fiber composite, 50 g of fly ash and 30 g of rice husk ash were mixed, stirred at 200 rpm for 15 min, and then 10 g of sodium lignin sulfonate water reducer and 22 g of UEA type expansion agent were added, and stirred at 200 rpm for 15 min to obtain a low shrinkage anti-cracking material additive.
[0069] Comparative Example 1:
[0070] Compared with Example 1, this comparative example does not add the straw powder composite during the preparation process of the low shrinkage and anti-cracking material additive, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally the low shrinkage and anti-cracking material additive is obtained.
[0071] Comparative Example 2:
[0072] Compared with Example 1, this comparative example only replaces "8g of sodium silicate nonahydrate" with "80g of sodium silicate nonahydrate", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a low shrinkage and anti-cracking material additive is obtained.
[0073] Comparative Example 3:
[0074] Compared with Example 1, the modified fiber composite was not added in the preparation process of the low shrinkage anti-cracking material additive in this comparative example, and the remaining steps and parameters were the same, which will not be repeated in this comparative example, and finally the low shrinkage anti-cracking material additive was obtained.
[0075] Comparative Example 4:
[0076] Compared with Example 1, this comparative example only replaces "30g wheat straw, 10g corn straw and 8g rice straw" with "48g wheat straw", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a low shrinkage and anti-cracking material additive is obtained.
[0077] Comparative Example 5:
[0078] Compared with Example 1, this comparative example only replaces "10g polypropylene fiber, 10g polyester fiber and 20g basalt fiber" with "40g polypropylene fiber", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a low shrinkage and anti-cracking material additive is obtained.
[0079] Comparative Example 6:
[0080] Compared with Example 1, this comparative example only replaces the "modified fiber composite" with "polypropylene fiber", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a low shrinkage and crack-resistant material additive is obtained.
[0081] Performance Testing:
[0082] Splitting tensile performance test:
[0083] With reference to the test standard GB / T50081-2002 "Test methods for mechanical properties of ordinary concrete", the low shrinkage and crack-resistant material additives prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were made into concrete, and the splitting tensile performance test was carried out to calculate the splitting tensile strength.
[0084] Splitting tensile strength calculation formula:
[0085] Among them, f ts is the concrete splitting tensile strength, in MPa; F is the specimen failure load, in N; A is the specimen splitting surface area, in mm 2 ;
[0086] Uniaxial compression test:
[0087] The low shrinkage and crack-resistant material additives prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were made into cylindrical test pieces, and tested using a HW-1000kN universal material testing machine to calculate their 28d compressive strength.
[0088] The formula for calculating the compressive strength is:
[0089] Where R c is the compressive strength, in MPa; P cis the maximum load of the specimen under pressure, in N; A is the cross-sectional area of the specimen, in mm 2 .
[0090] Water absorption performance test:
[0091] Referring to the test standard of Appendix F "Test method for water absorption of concrete" of DB32 / T3696-2019, the low shrinkage and anti-cracking material additives prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were made into concrete specimens, and the water absorption performance test was carried out to calculate the water absorption rate of the specimens.
[0092] Table 1 Summary of experimental data in Examples 1 to 6 and Comparative Examples 1 to 6
[0093] project Splitting tensile strength / MPa Compression strength / MPa Water absorption / % Example 1 6.47 86.47 3.2 Example 2 6.14 86.25 3.3 Example 3 5.96 85.31 3.4 Example 4 5.38 87.12 3.5 Example 5 6.32 75.36 3.2 Example 6 5.74 75.96 3.3 Comparative Example 1 3.12 52.47 5.4 Comparative Example 2 4.78 60.69 5.6 Comparative Example 3 3.65 56.47 6.1 Comparative Example 4 5.64 65.12 4.9 Comparative Example 5 5.12 72.36 5.3
[0094] Data Analysis:
[0095] As can be seen from Table 1, the low shrinkage anti-cracking material additive prepared by the present invention has better splitting tensile strength and mechanical properties;
[0096] In Comparative Example 1, since the straw powder composite was not added during the preparation of the low shrinkage and crack-resistant material additive, it can be seen from Table 1 that the splitting tensile strength and mechanical properties of the low shrinkage and crack-resistant material additive used in the preparation of concrete decreased. This may be because the main component of straw is fiber. Straw is added to concrete as fiber to form a fiber network, which can effectively inhibit the expansion of microcracks during the hardening of concrete. When concrete is subjected to external force, these fibers can absorb part of the tensile stress, improve the toughness of concrete, and reduce the generation of cracks. After the straw powder is modified with sodium silicate nonahydrate, the mechanical properties increase. This may be because sodium silicate nonahydrate can form a uniform and dense protective layer on the fiber surface and penetrate into the internal pores of the fiber to increase the density of the material, and synergize with cellulose during the modification process, thereby enhancing the toughness of the fiber. At the same time, sodium silicate can improve the interfacial adhesion between the fiber and the matrix and reduce the generation of interfacial cracks, so the mechanical properties of the prepared concrete are significantly improved;
[0097] In Comparative Example 2, since only "8g sodium silicate nonahydrate" is replaced by "80g sodium silicate nonahydrate", it can be seen from Table 1 that the splitting tensile strength and mechanical properties of the prepared low shrinkage anti-cracking material additive used in concrete preparation are reduced. This may be because excessive sodium silicate nonahydrate inhibits the crystallization of cellulose and affects the crystal structure of cellulose, resulting in reduced mechanical strength of the fiber and even fracture or deformation, and excessive sodium silicate nonahydrate particles have poor dispersion on the fiber surface and are prone to agglomeration, resulting in uneven fiber structure, which is not conducive to the adhesion of the fiber to the matrix, resulting in stress concentration, resulting in interface peeling or cracking, and thus having an adverse effect on the mechanical strength of the prepared concrete;
[0098] Comparative Example 3 Since the modified fiber composite was not added during the preparation of the low shrinkage and crack-resistant material additive, it can be seen from Table 1 that the splitting tensile strength and mechanical properties of the low shrinkage and crack-resistant material additive used in concrete preparation decreased. This may be because polypropylene fiber, polyester fiber and basalt fiber can play a certain degree of reinforcement role and inhibit the formation of shrinkage cracks. The use of mesoporous silica modified fiber can increase the viscosity of concrete due to the large specific surface area of mesoporous silica, effectively improve the bonding force between the additive and concrete, and improve the crack resistance;
[0099] Comparative Example 4 Since only "30g wheat straw, 10g corn straw and 8g rice straw" were replaced with "48g wheat straw", it can be seen from Table 1 that the splitting tensile strength and mechanical properties of the prepared low shrinkage anti-cracking material additive used in concrete preparation decreased. This may be because different types of straw have different chemical compositions, such as different proportions of cellulose, hemicellulose and lignin. This diversity can provide more comprehensive physical and chemical properties, help improve the microstructure of concrete, and enhance its resistance to cracks;
[0100] In Comparative Example 5, since only "10g polypropylene fiber, 10g polyester fiber and 20g basalt fiber" are replaced with "40g polypropylene fiber", it can be seen from Table 1 that the mechanical properties of the low shrinkage and crack-resistant material additive used in concrete preparation are reduced. This may be because the random distribution of the composite fiber increases the complexity of the concrete and improves its toughness. The addition of each fiber can form additional support points in the concrete matrix, reduce stress concentration, and thus reduce the formation of cracks.
[0101] In Comparative Example 6, since only the "modified fiber composite" is replaced with "polypropylene fiber", it can be seen from Table 1 that the splitting tensile strength and mechanical properties of the prepared low shrinkage and crack-resistant material additive used in concrete preparation decrease, and the water absorption rate of the prepared concrete increases. This may be because the silane coupling agent can significantly enhance the bonding force between the fiber and the matrix and improve the overall strength of the composite material by forming an interface layer on the fiber surface; some fibers will form a weak area at the interface between the additive and the matrix, and water molecules can easily invade this interface through the fiber, resulting in an increase in water absorption. After adding mesoporous silica, the matrix and aggregate are more adhered, reducing the adverse effects of water on concrete. Without modification, the addition of additives will increase the water absorption rate of concrete.
[0102] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0103] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A low shrinkage anti-cracking material additive, characterized in that: The method comprises the following raw materials in parts by weight: 20-25 parts of straw powder compound, 15-20 parts of modified fiber compound, 45-50 parts of fly ash, 15-30 parts of rice husk ash, 6-10 parts of water reducing agent and 18-22 parts of expansion agent; The straw powder composite is prepared from sodium silicate nonahydrate, wheat straw, corn straw and rice straw; The modified fiber composite is prepared from polypropylene fiber, polyester fiber, basalt fiber and mesoporous silica.
2. The low shrinkage and crack-resistant material additive according to claim 1, characterized in that: The preparation method of the straw powder composite is as follows: Step A1. Cut wheat straw, corn straw and rice straw into small pieces, put them into a grinder, grind them, and dry them at 70-80°C for 3-5h to obtain straw powder; Step A2. Sodium silicate nonahydrate is dissolved in water at 28-32°C, and then straw powder is added, reacted for 4-6 hours, stirred at 200-300 rpm for 15-18 minutes every half an hour, and dried at 90-100°C for 5-8 hours to obtain a straw powder composite.
3. The low shrinkage anti-cracking material additive according to claim 2, characterized in that: In step A1, the mass ratio of wheat straw, corn straw and rice straw is 30-35:10-15:8-12; The particle size of the straw powder in step A1 is 10-30 mm.
4. The low shrinkage and crack-resistant material additive according to claim 2, characterized in that: The mass ratio of sodium silicate nonahydrate, water and straw powder in step A2 is 8-10:250-300:45-50.
5. The low shrinkage and crack-resistant material additive according to claim 1, characterized in that: The preparation method of the modified fiber composite is as follows: Step B1. Take polypropylene fiber, polyester fiber and basalt fiber, and irradiate them with electron beam to obtain pretreated composite fibers; Step B2. Place the silane coupling agent in a 78%-85% ethanol solution, stir at 120-150rpm for 10-15min, then add the mesoporous silica, and continue stirring for 70-80min; then add the pretreated composite fiber, and ultrasonically treat for 40-50min, filter, wash, and dry at 70-80°C for 8-12h to obtain a modified fiber composite.
6. The low shrinkage and crack-resistant material additive according to claim 5, characterized in that: The mass ratio of the polypropylene fiber, the polyester fiber and the basalt fiber in step B1 is 10-15:10-15:20-30; The irradiation dose of the electron beam irradiation in step B1 is 200-250 kGy, and the irradiation time is 8-10 s.
7. The low shrinkage and crack-resistant material additive according to claim 5, characterized in that: The mass ratio of the silane coupling agent, the ethanol solution, the mesoporous silica and the pretreated composite fiber in step B2 is 55-65:95-105:1-1.5:4.5-5.
5.
8. The low shrinkage and crack-resistant material additive according to claim 1, characterized in that: The water reducer is any one of a polycarboxylate water reducer and a sodium lignin sulfonate water reducer.
9. The low shrinkage and crack-resistant material additive according to claim 1, characterized in that: The expansion agent is any one of a calcium oxide expansion agent, a CSA expansion agent and a UEA expansion agent.
10. The low shrinkage and crack-resistant material additive according to claim 1, characterized in that: The preparation method of the low shrinkage anti-cracking material additive is as follows: The straw powder composite, modified fiber composite, fly ash and rice husk ash are mixed, stirred at 100-200 rpm for 10-15 minutes, and then a water reducer and an expansion agent are added, and stirred at 100-200 rpm for 10-15 minutes to obtain a low shrinkage anti-cracking material additive.
Citation Information
Patent Citations
A multi-effect self-waterproofing additive for concrete structures with self-healing capabilities
CN109485299B